Tunable Trimers: Using Temperature and Pressure to Control Luminescent Emission in Gold(I) Pyrazolate‐Based Trimers. Issue 51 (21st October 2014) - Woodall, Christopher H.; Fuertes, Sara; Beavers, Christine M.; Hatcher, Lauren E.; Parlett, Andrew; Shepherd, Helena J.; Christensen, Jeppe; Teat, Simon J.; Intissar, Mourad; Rodrigue‐Witchel, Alexandre; Suffren, Yan; Reber, Christian; et al.
Abstract A systematic investigation into the relationship between the solid‐state luminescence and the intermolecular Au⋅⋅⋅Au interactions in a series of pyrazolate‐based gold(I) trimers; tris(μ2‐pyrazolato‐N, N′)‐tri‐gold(I) (1), tris(μ2‐3, 4, 5‐ trimethylpyrazolato‐N, N′)‐tri‐gold(I) (2), tris(μ2‐3‐methyl‐5‐phenylpyrazolato‐N, N′)‐tri‐gold(I) (3) and tris(μ2‐3, 5‐diphenylpyrazolato‐N, N′)‐tri‐gold(I) (4) has been carried out using variable temperature and high pressure X‐ray crystallography, solid‐state emission spectroscopy, Raman spectroscopy and computational techniques. Single‐crystal X‐ray studies show that there is a significant reduction in the intertrimer Au⋅⋅⋅Au distances both with decreasing temperature and increasing pressure. In the four complexes, the reduction in temperature from 293 to 100 K is accompanied by a reduction in the shortest intermolecular Au⋅⋅⋅Au contacts of between 0.04 and 0.08 Å. The solid‐state luminescent emission spectra of 1 and 2 display a red shift with decreasing temperature or increasing pressure. Compound 3 does not emit under ambient conditions but displays increasingly red‐shifted luminescence upon cooling or compression. Compound 4 remains emissionless, consistent with the absence of intermolecular Au⋅⋅⋅Au interactions. The largest pressure induced shift in emission is observed in 2 with a red shift of approximately 630 cm−1 per GPa between ambient and 3.80 GPa. The shifts in all the complexes can be correlated with changes in Au⋅⋅⋅Au distance observed by diffraction.